A new European banana regime - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The European Union (EU) is currently the main market outlet for imported bananas, with an estimated annual turnover of ECU 2 billion ($1.8 billion) in 1996 (excluding trade between EU members). By 1999, European demand...